Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae) - Handru, Alan; Nugroho, Hari; Saito-Morooka, Fuki; Ubaidillah, Rosichon; Kojima, Jun-Ichi (Zootaxa, 2020)
Taxonomy of eusocial wasps (Polistinae and Vespinae) occurring in Sulawesi Island, the central island of Wallacea, is reviewed. Sixteen (12 polistine and four vespine) species are recognized. Polistes (Polistella) stigma, known to be widely distributed in southern Asia and Australasia, is newly recorded for Sulawesi Island. A key to the Sulawesian eusocial wasp species is provided. Their biogeographical characteristics are discussed to show that the Sulawesian eusocial wasp fauna is composed of Oriental elements.